Translating “Swear & Curse Words” from Indonesian Literature into English - Erna Wiles (Universitas Veteran Bangun Nusantara, 2019)
Translating swear and curse words in a literary work is very challenging. Not only does it depict real life in the past, but it is also socio-culturally bound. Some words might have become archaic. To seek the best strategy, an analysis of the translation of Pramoedya Ananta Toer’s BumiManusia into “This Earth of Mankind” by Max Lane was performed. Strategies employed when a swear or curse words do not have the equivalence in the target language are as follows; 1) translate by using the literal form; 2) substitute the swear words from the target language with the closes features when context can help the readers understand the meaning and add and exclamation mark to deliver the emotive meaning; 3) add a lexical emphasis to preserve the emotive meaning; 4) use a completely different form of swear words but have the same meaning; 5) for swear and curse words using animal names can be replaced with any forms of swear and curse words but with the same meaning; and 6) swear words in a form of onomatopoeia can be retained as it is as long as the context allows.